Effects of Zinc Methionine Hydroxy Analog Chelate on Laying Performance, Serum Hormone Levels, and Expression of Reproductive Axis Related Genes in Aged Broiler Breeders - Yang, Bowen; Gong, Jiangang; Jing, Jialin; Hao, Yanshuang; Li, Shupeng; Liu, Guanzhong; Feng, Zhihua; Zhao, Guoxian (Frontiers in Veterinary Science, 2022)
Inorganic zinc supplements are commonly used in poultry feeds, but their low utilization results in overusing of zinc supplements. Thus, a novel zinc methionine hydroxy analogue chelate (Zn-MHA) was studied in the present experiment to evaluate its effects on performance, serum hormone indexes and reproductive axis related genes in broilers breeders, in order to provide a new perspective for the substitution of inorganic zinc. A total of 480 56-wk-old Hubbard breeders were fed a basal diet (Zn: 27.81 mg/kg) without extra zinc for 2 wk to depletion storage zinc from the body, and then allocated to four treatments consisting of 6 replicates of 20 birds each for 10 wk. Four treatment diets included: 25, 50, and 75 mg/kg of Zn-MHA and 100 mg/kg of zinc sulfate (ZnSO4), respectively. The results indicated that the egg weight and feed conversation ratio increased linearly (P < 0.05) by increasing Zn-MHA level. The eggshell thickness increased linearly with the addition of Zn-MHA in the diet (P < 0.05). Compared to the ZnSO4 group, the albumen height and Haugh unit of the 50 and 75 mg/kg Zn-MHA group increased (P < 0.05). There was significant improvement in fertility of 75 mg/kg Zn-MHA group (P < 0.05). And offspring weight of the 50 and 75 mg/kg Zn-MHA group increased (P < 0.05). Besides, serum sex hormone levels increased linearly with the increase in Zn-MHA supplementation (P < 0.05). No significant effect on the ovarian weight or the number of follicles in broiler breeders were observed by supplementing Zn-MHA. Compared to the ZnSO4 group, dietary supplementation with 75 mg/kg of Zn-MHA up-regulated the FSHR mRNA LHR mRNA in the granular layer of follicles (P < 0.05). Dietary supplementation of Zn-MHA had no effects on mRNA expression of PRLR mRNA in ovary. Therefore, Zn-MHA can be a potential substitute for ZnSO4, which obtained better laying and reproduction performance by regulating the expression of reproductive axis related genes and serum hormone levels.